The structure, processes, and outcomes of stroke rehabilitation in Ghana: A study protocol - Yarfi, Cosmos; Nyante, Gifty Gyamah; Rhoda, Anthea (Frontiers in Neurology, 2022)
Background Conventional and complementary treatments are often used in rehabilitation for persons with stroke. Conventional treatment makes use of medications, physiotherapy, occupational, speech and diet therapies while complementary treatment makes use of homeopathy, naturopathy, massage and acupuncture. The structure, process and outcomes of stroke rehabilitation using conventional or complementary treatments have not been empirically investigated in Ghana. Aims To investigate the structure, process and outcomes of stroke rehabilitation at the Korle Bu Teaching Hospital (KBTH) in Accra and Kwayisi Christian Herbal Clinic (KCHC) in Nankese-Ayisaa, Ghana and to explore experiences of persons with stroke. Methods A mixed methods approach involving a cross sectional, hospital-based cohort and qualitative exploratory studies. The objectives of the study will be achieved using three phases: Phase one will recruit health professionals and gather information on the structure and process of stroke rehabilitation at conventional and complementary hospital using adapted questionnaires. Phase two will determine outcomes of persons with stroke attending a conventional and complementary hospital facility at baseline, two, three- and six-months follow-up using outcome measures based on the International Classification of Functioning, Disability and Health (ICF) model. Phase three will explore experiences of persons with stroke who use complementary or conventional treatment using an interview guide. Data Analysis IBM SPSS Statistics Version 27 will be used to analyse the data using descriptive and inferential statistics. Repeated measures of ANOVA analysis will be used to determine differences between variables at baseline, two, three- and six-months post stroke. The qualitative data will be transcribed and entered into Atlas Ti version 9.0. The data will be coded and analysed using thematic areas that will be generated from the codes. Conclusion The study protocol will provide a comprehensive overview of structure, process and outcomes of stroke rehabilitation in Ghana: incorporating both conventional and complementary treatment and rehabilitation into the stroke recovery journey. It will also inform clinical practice, with new insights on the experiences of persons with stroke based on their choice of rehabilitation pathway.